Reatores de biofilme utilizados no tratamento de efluentes e na geração de hidrogênio - Silva, André Jesus Marques da (Universidade Federal de São Carlos, 2023)
The increase in domestic and industrial waste has accompanied the rapid growth of population and industrial development since the beginning of the 20th century. Speaking of the century, the correct disposal of urban waste is one of the greatest challenges for humanity in the 21st century, and with each decade the problem becomes more and more complex. The incorrect disposal of both liquid and solid waste causes environmental degradation and contamination, thus generating serious risks to public health and the well-being of the population. In addition, one can think of adding value to this waste, transforming it into energy, generating jobs, contributing to the economy, and strengthening the sustainable development of the productive sector. If the emphasis is given to liquid waste, or industrial effluents, it is immediately revealed that they are one of the main sources of direct and continuous entry of pollutants in aquatic ecosystems. One possible treatment process for these effluents is through bioreactors specifically designed to support a biologically active environment, i.e. where bacteria and protozoa (the biomass) can grow and consume some (or all) contaminating substances. In this context, the present work aimed to present, through a literature review, the most recent and relevant contributions on wastewater treatment and H2 production in biofilm reactors. The forms of wastewater treatment (physical, chemical, biological) were reviewed and, in particular, the reactors that use the anaerobic digestion process. The bibliographical research indicated that there is a great diversity of works that use the most varied substrates for the treatment, clearly showing that this is an area still under technological development. In general, anaerobic reactors are highly effective in effluent treatment, producing at the same time a large amount of H2, in an average, according to studies, of about 80%.
Biofilm reactors used in wastewater treatment and hydrogen generation
Keywords: Redução de hidrogênio; Demanda química de oxigênio; Reator de biofilme; Digestão anaeróbia; Efluentes; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA